2006
DOI: 10.1159/000095731
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Agreement of Schizophrenia Spectrum Disorders among Chronic Patients with Functional Psychoses

Abstract: Background: To investigate whether diagnostic agreement across different diagnostic systems improves in a sample of chronic patients suffering from functional psychosis compared to first-admitted patients. Sampling and Methods: Among 353 patients with a history of functional psychosis, a subset of 100 individuals (35 women and 65 men) were randomly sampled and assessed using the Operational Criteria Checklist for Psychotic Illness and Affective Illness (OPCRIT). Based on the OPCRIT diagnoses the subjects suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
(14 reference statements)
1
22
0
Order By: Relevance
“…The higher frequency of diagnosis of schizophrenia according to ICD-10 than DSM-IV or DSM-III-R has also been reported in two additional studies [17,18] , although other studies failed to detect this difference [2,13,[19][20][21] . Indeed, ICD-10 criteria for schizophrenia seem to be less restrictive.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The higher frequency of diagnosis of schizophrenia according to ICD-10 than DSM-IV or DSM-III-R has also been reported in two additional studies [17,18] , although other studies failed to detect this difference [2,13,[19][20][21] . Indeed, ICD-10 criteria for schizophrenia seem to be less restrictive.…”
Section: Discussionmentioning
confidence: 60%
“…Two other studies found a high congruence, with kappa values of 0.86 and 0.87 [20,34] . However, it should be noted that the sample of one of these studies [20] was composed by chronic patients.…”
Section: Discussionmentioning
confidence: 83%
“…SDs were assessed with the EASE scale, conducted by one of us (Julie Nordgaard), an experienced psychiatrist with psychometric research experience [45,46] and trained to expert level in the use and teaching of the EASE scale. For the purpose of the analysis, we looked only for the presence or absence (not severity or duration) of the EASE items (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The issue of validity has been the object of a number of studies [12,13], and has also been questioned by many scholars, who lamented the marginalization of the knowledge of classical psychopathology and the decline in psychiatrists' expertise and capacity for individualized, person-centred assessment and treatment [14,15,16]. Indeed, vast domains of human experience have been deleted from the official nosography, resulting in a lack of a comprehensive account of human subjectivity [17].…”
Section: Introductionmentioning
confidence: 99%